The Role of Nrf2 (Nfe2l2) In the Physiological and Biochemical Pathways Underlying Oxidative Stress-Induced Male Infertility - Rasha Hamzah Abdulhussein; Zahraa Hamid Mohan Al-Gawwam; Rafid A. Taj-Aldeen; Hameda Abd Almahdi Ghazi (International Journal of Medical Science and Dental Health, 2025)
Male infertility related to oxidative stress begins with a severe imbalance between the overwhelming generation of reactive oxygen species and restricted capacity of endogenous antioxidant defenses. A chain reaction is initiated by this oxidative imbalance in structural and functional damages to the sperm, such as peroxidation of lipids in the plasma membrane, oxidative modifications to proteins, mitochondrial dysfunction, and fragmentation to both nuclear and mitochondrial DNA. Such molecular damages motility of sperm reduce fluidity in membranes and general fertility thus leads ultimately reduces reproductive success. NRF2 (nuclear factor erythroid 2-related factor 2) has been described as a master regulator in controlling cellular antioxidant responses and hence playing central protective roles against oxidative stresses. In conditions of oxidation NRF2 separates from its cytoplasmic repressor Keap1 moves to nucleus binds on ARE then induces transcription detoxification as well as antioxidant genes including HO-1 heme oxygenase-1 NAD(P)H quinone oxidoreductase -1 superoxide dismutase glutathione peroxidase. It is this signaling pathway that maintains redox homeostasis and protection against cellular damage induced by ROS. On the other hand, impaired NRF2 activation or polymorphisms in the NFE2L2 gene have been associated with increased oxidative stress as well as increased sperm DNA damage and decreased sperm quality. Therefore, elucidating the NRF2 signaling cascade provides a promising approach for developing targeted diagnostic markers and therapeutic interventions. Future strategies may include combining NRF2 activity assessment with advanced redox biomarkers and personalized antioxidant therapy to improve the prevention, diagnosis, and treatment of male infertility caused by oxidative stress, thereby providing more precise and effective reproductive healthcare solutions.